ENGAGING LEARNERS IN WRITING PROCEDURE TEXT: HARNESSING THE POWER OF DO IT YOURSELF (DIY) VIDEOS AT IAIN PALOPO: HARNESSING THE POWER OF DO IT YOURSELF (DIY) VIDEOS AT IAIN PALOPO - Zainuddin, Andi Husni A.; Pirol, Abdul; Rusdiansyah, Rusdiansyah (English Language, Linguistics, and Culture International Journal, 2024)
This research aims to determine whether the Do It Yourself video effectively improves writing skills in the procedure text at the second semester of the English Language Education Study Program IAIN Palopo. This research adopted the pre-experimental method. The sample consisted of thirty students. The Do It Yourself video was used as a medium in this research. The researcher collected the data through pre-test, treatment, and post-test. SPSS 22 edition was used to perform statistical analysis on the data. Investigation revealed that the mean post-test score is higher than the pre-test (47.80 < 81.36). Besides, the value of the t-count is higher than the value of the t-table. The result of the student's scores on the post-test became more elevated than opposed tests representing the treatment's effectiveness in helping the learners improve their writing skills. It could be summarized that using the Do It Yourself video significantly improved the students' writing skills, especially in writing procedure text. This research strongly emphasizes for the next researcher to examine the use of DIY videos for different skills imaginatively.